Linking land reform and rural development to poverty alleviation in the rural areas - Makgata, Makgorometje Augustine (My University, 2014)
The issue of rural poverty is deeply rooted in the skewed distribution of the resources in the rural areas. The majority of rural people do not have access to the basic services like health, water, electricity, education etc. the inequalities constitute a barrier to progress, and indeed there is some evidence to indicate that the extreme inequality acts as bottleneck to development. Land Reform and Rural Development programmes have been initiated in the rural areas to alleviate poverty, although they have been subject to hot debates in many countries. This is due to the fact that most of these programmes have fallen short of expectations, especially of the intended beneficiaries. This discourse attempts to link Land Reform and rural development to poverty alleviation. This is done by reviewing literature on land reform and rural development, analysing the case of Tarlton land Redistribution project and recommendations on the best practice for poverty alleviation through an integrated approach towards land reform and rural development.
Keywords: Rural development--South Africa